ANALISIS PROSES REKRUTMEN DAN SELEKSI TENAGA KESEHATAN TIM NUSANTARA SEHAT DALAM PROGRAM NUSANTARA SEHAT KEMENTERIAN KESEHATAN REPUBLIK INDONESIA - Hendro Nurcahyo; Antono Suryoputro; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Nusantara Health Program is a program that potentially solve the problems of distribution health workers in Indonesia. The Ministry of Healthhas targets in 2015 will deliver about 960 health workers were divided into two periods. The health worker from Nusantara Sehat team will occupied 120 health centers in the area of DTPK and DBK. In the first and second period of implementationin 2015, the number of health workers from Nusantara Sehat team in placement, do not meet the targets, there was only 694 health workers from 950 health workers has planned. This problem causedamount of health centers has minimal number of medical personnel. This problem is about the fulfillment of human resources in health personnel resources that will be placed as Nusantara Sehat Team. The purpose of this study is to describe how the recruitment and selection process overview Health Worker of Nusantara Sehat team, a Program from Ministry of Health of the Republic of Indonesia. This is a qualitative research with in-depth interviews. Interviews were conducted to the informant directly related to the recruitment and selection process of Nusantara Sehat program, there are Pusrengun BPPSDMK in health ministry of health of the Republic of Indonesia and Nusantara Sehat Program applicants. The results showed thatthe publication forming of recruitment has been using way where everyone can knows and the selection process conducted by two stages with knockout system. Recruitment and selection process has some obstacles, there still a lack of both doctors and dentists. This obstacle happened because the content of publication recruitment can not make applicants interested to apply.